2021
DOI: 10.1002/mgg3.1850
|View full text |Cite
|
Sign up to set email alerts
|

A genotype and phenotype analysis of SMAD6 mutant patients with radioulnar synostosis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Patients with RUS 9 , 13 (cases, N = 93) (probands, N = 77, Table 1 ) are most frequently characterised by bilateral RUS (69%; isolated ( N = 42/61), familial ( N = 22/32)), followed by unilateral left-sided RUS in sporadic patients ( N = 15/42, 36%) versus right-sided RUS ( N = 4/42, 10%), while no susceptibility for left- or right-sided RUS was observed in families ( N = 5/32, 16%). Affected individuals within a single pedigree can show both bilateral and unilateral RUS.…”
Section: Clinical Phenotype Of Patients With Smad6-deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with RUS 9 , 13 (cases, N = 93) (probands, N = 77, Table 1 ) are most frequently characterised by bilateral RUS (69%; isolated ( N = 42/61), familial ( N = 22/32)), followed by unilateral left-sided RUS in sporadic patients ( N = 15/42, 36%) versus right-sided RUS ( N = 4/42, 10%), while no susceptibility for left- or right-sided RUS was observed in families ( N = 5/32, 16%). Affected individuals within a single pedigree can show both bilateral and unilateral RUS.…”
Section: Clinical Phenotype Of Patients With Smad6-deficiencymentioning
confidence: 99%
“…Surgical correction is frequently necessary to prevent complications 24 such as developmental delay, facial abnormality, sensory, respiratory and neurological dysfunction, anomalies affecting the eye, and psychological disturbances 25 . Finally, congenital RUS, also referred to as fused forearm bones, is a rare condition with ~500 cases reported in literature 9 , 13 , 26 . This malformation, usually diagnosed before the age of 5 years, is not life-threatening, but corrective surgery and/or medication to control pain might, in some cases, improve the quality of life 13 .…”
mentioning
confidence: 99%
“…Approximately 10% of them had a family history with an AD mode of inheritance. In 2019 and a recent study, 7,11 we identified 41.03% RUS pedigrees and 13.99% patients with sporadic RUS harboring SMAD6 variants, approximately 2.63% RUS pedigrees and 0.51% patients with RUS sporadic caused by mutant NOG, and 10.09% patients RUS sporadic caused by chromosome aneuploidy. We still have half of RUS pedigrees and three-quarters of patients with sporadic RUS with unknown genetic cause.…”
Section: Discussionmentioning
confidence: 88%
“…7,11 The inclusion criteria included diagnosis of RUS (through x-ray imaging) and absence of identifiable syndromes, such as Apert/Crouzon/Pfeiffer syndrome, 12 Holt-Oram syndrome, 13 William syndrome, 14 Ehlers-Danlos Syndrome, 15 and other obvious dysmorphic syndromes. Meanwhile, patients with RUS with mutant SMAD6 or NOG, 7,11 chromosome aneuploidy, 7 or obvious intellectual disability were excluded from this study. We did not encounter any patient with RUSAT in the collection of hundreds of specimens from patients with RUS.…”
Section: Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation